Factors influencing consumption for life insurance - Teo, Hong Li; Tan, Jia Qi (2022)
This paper objective is to determine the relationship between the demographic factors which are income, education level, size of family and age with the consumption of life insurance. This research will be analyzed through collecting the primary data with questionnaire. There will be a Multiple Linear Regression (MLR) to explain the relationship between the variables. Under this research, it was founded that the 4 demographic factors including income, education level, size of family and age are having a positive relationship with the consumption of life insurance.